Proof for 1=2 solution: a=b a^2=ab (a^2)-(b^2)=ab-(b^2) (a+b)(a-b)=b(a-b) => a=b .....(1) a+b=b from equation (1) b+b=b 1+1=1 2=1!!! Warning : Opps if a=b then (a+b) *0 = b *0 so 0/0

i also prove 2+2=5 here we know that 0=0 -20 = -20 (the is no problem to know what that) 16-36 = 25-45 (we Can Write The no problem still) (4^2)-2(4)(9/2)+{(9/2)}^2=(5^2)-2(5)(9/2)+{(9/2)}^2 (just open it with the formula of (a-b)^2 which is ballance both side) (4-9/2)^2 = (5-9/2)^2 (close the third equestion as (a-b)^2) taking squre root both side 4-9/2= 5-9/2 ( after that -9/2 is cancell) 4=5 we can write that 2+2= 5 Have FUN